2019
DOI: 10.1177/1179544119867922
|View full text |Cite
|
Sign up to set email alerts
|

The Combined Effect of Body Mass Index and Tibial Slope Angles on Anterior Cruciate Ligament Injury Risk in Male Knees: A Case-Control Study

Abstract: Introduction: Tibial slope angles (TSAs) have been identified as potential risk factors of anterior cruciate ligament (ACL) injury in the literature. A higher body mass index (BMI) might increase the risk of ACL tear because of greater axial compressive force. The aim of this study was to determine the relationship of these factors and the combined effect of BMI and TSA in determination of risk potential for ACL injury. Methods: The preoperative magnetic resonance (MR) images of 81 ACL-injured male knees and o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 51 publications
0
6
0
Order By: Relevance
“…At present, many studies have assessed the morphological risk factors for anterior cruciate ligament (ACL) rupture. Risk factors for ACL rupture include a narrow intercondylar notch, lower notch width index (NWI), a smaller tibial eminence, a stenotic intercondylar notch shape, and increased tibial slope [2, 3, 5, 7, 12, 14]. The results of these studies can help individuals with these risk factors prevent ACL injuries during exercise [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…At present, many studies have assessed the morphological risk factors for anterior cruciate ligament (ACL) rupture. Risk factors for ACL rupture include a narrow intercondylar notch, lower notch width index (NWI), a smaller tibial eminence, a stenotic intercondylar notch shape, and increased tibial slope [2, 3, 5, 7, 12, 14]. The results of these studies can help individuals with these risk factors prevent ACL injuries during exercise [5].…”
Section: Introductionmentioning
confidence: 99%
“…The results of these studies can help individuals with these risk factors prevent ACL injuries during exercise [5]. The increased tibial slope is related to ACL injuries as the increased tibial slope can cause a greater anterior displacement of the tibia in sports [10, 12, 13]. In contrast, a decreased tibial slope is a risk factor for PCL rupture because an increased tibial slope can better prevent the tibia from moving backward excessively and avoid PCL injury [4, 9].…”
Section: Introductionmentioning
confidence: 99%
“…Another anthropometric risk factor for ACL injury in humans is increased body mass index (BMI), 6,36,37 and this appears to be a stronger risk factor in females than in males. 6 How elevated BMI increases the risk of ACL injury is unclear.…”
Section: Discussionmentioning
confidence: 99%
“…The association between ACL injury and higher BMI was significant compared to athletes who did not have an ACL injury in this group. Elevated weight and BMI values have been found to be significantly associated with ACL injuries, especially in male individuals and associated with other intra-articular injuries observed during ACL reconstructions [13,27]. Further observational studies have shown that taller or heavier subjects are at a greater risk for injury because of the greater forces acting on the muscles, bones, and the connective tissues [28].…”
Section: Discussionmentioning
confidence: 99%
“…Further observational studies have shown that taller or heavier subjects are at a greater risk for injury because of the greater forces acting on the muscles, bones, and the connective tissues [28]. Other associated anatomical factors which were studied with BMI like the lateral tibial slope (LTS), medial tibial slope (MTS) and posterior tibial slope (PTS) were also predictive of ACL injury risk [27,28]. Our data confirms that BMI as a modifiable risk factor that should be improved and included in non-contact ACL injury prevention strategies.…”
Section: Discussionmentioning
confidence: 99%